THE NARRATIVE MODELS OF THE HEROINE’S WAY IN RUSSIAN FAIRY TALE (Proceedings of Southern Federal University. Philology, 2026)
10.18522/1995-0640-2026-1-131-142As part of the study of female initiation in the folk tradition, four models of the heroine’s way in the Russian fairy tale are proposed, highlighted on work on the way of the hero V. Ya Propp and J. Campbell and to analyze plot groups with an active central female character. The set of plots and the description of models are based on the structure of the female character and on the family and the age status of the heroine. The above models retained the features of ancient family and generic relationships. So these models can be used in a further more in depth analysis of fabulous plots both on Russian folklore material and on the material of other cultures. This will open up opportunities for wider generalizations and comparisons. The article also presents a brief overview of the concept of the heroine’s way in two popular modern works and an assessment of their degree of application for the analysis of actual material within the folkloristics. Key words: fairy tale, heroine, female character, way model, initiation, folklore